2015
DOI: 10.1038/jcbfm.2015.169
|View full text |Cite
|
Sign up to set email alerts
|

STAT-Dependent Upregulation of 12/15-Lipoxygenase Contributes to Neuronal Injury after Stroke

Abstract: Oxidative stress is a major brain injury mechanism after ischemic stroke. 12/15-lipoxygenase (12/15-LOX) is a key mediator of oxidative stress, contributing to neuronal cell death and vascular leakage. Nonetheless, the mechanism leading to its upregulation is currently unknown. We show here that Signal Transducers and Activators of Transcription (STATs), specifically STAT6 and possibly STAT1, increase transcription of 12/15-LOX in neuronal cells. Both p-STAT6 and -1 bound to specific STAT binding sites in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 40 publications
2
22
0
1
Order By: Relevance
“…The pSTAT6 staining partially overlapped with DAPI nuclei staining (Supplemental Figure 2, C-E). The pSTAT6 signal was also noted in some Iba1cells in both nonstroke and stroke brains, consistent with a previous report suggesting STAT6 activation in other types of cells in diseased or aging human brains (14).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The pSTAT6 staining partially overlapped with DAPI nuclei staining (Supplemental Figure 2, C-E). The pSTAT6 signal was also noted in some Iba1cells in both nonstroke and stroke brains, consistent with a previous report suggesting STAT6 activation in other types of cells in diseased or aging human brains (14).…”
Section: Resultssupporting
confidence: 91%
“…Interestingly, pSTAT6 signal was detected in Iba1cells in both stroke patients and nonstroke aged brain. This is consistent with a previous report by Jung et al that documented STAT6 expression in the peri-infarct region of brains from stroke patients (14). Jung et al's study -while it did not use cellular markers to specify cell type in human samples -reported STAT6 activation in oxidatively stressed neurons in culture, with elevated STAT6 activity leading to neuronal death.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The LcnRNA MEG3 was shown to be overexpressed in the brain of the MCAO mice, along with the upregulation of p53 and of 12/15-Lipoxygenase (12/15-LOX), two activators of cell death [103,104]. Specifically, MEG3 was found to interact with p53 during ischemia, allowing the activation of neuronal cell apoptosis.…”
Section: Rna-based Mechanisms In Ismentioning
confidence: 99%
“…Однако существуют и достаточно убедительные прямые доказательства индукции стволовости в ответ на оксидативный стресс [77][78][79]. Мы нашли доказательства активирующего действия оксидативного стресса для 34 генов из нашего списка: Abca1 [80], Acpp [81], Aldh1a1 [82], Alox15 [83], Arg2 [84], Blnk [46], Ccr3 [85], Cd200 [86], Cd55 [87], Col3a1 [88], Comp [89], Cp [90], Eef1a2 [91], Fgfr1 [92], Gas6 [93], Gstm3 [94], Igf1 [95], Igf2 [96], Il10 [97], Lyve1 [95], Mmp2 [98], Nfatc2 [99], Pde4d [100], Pdk4 [101], Per2 [102], Pon1 [103], Prg4 [104], Rragd [105], Selp [106], Serpinb1a [107], Serpinb2 [108,109], Slc2a4 [110], Tal1 [111], Wnt5a [112].…”
Section: индукция «генов стволовости» в условиях генерализованного клunclassified